WAVE REGIME IN THE COASTAL AREA OF DAI RIVER MOUTH AT QUANG NAM PROVINCE - Huu, Vu Cong; Hoan, Le Xuan (Vietnam Journal of Marine Science and Technology, 2018)
The calculations of wave characteristics have an important role in the study of coastal processes. The coastal area of Dai river mouth (Cua Dai) at Quang Nam province has been experiencing serious shoreline and beach changes that have effected on the socio-economic activities and people's lives. This research has calculated the characteristics of wave field in Cua Dai, Quang Nam by steady-spectrum wave model for the time period from 2002 to 2016 years. The model was verified by experimental data in the wave tank, measured wave data in Nha Trang - Khanh Hoa for 2 periods characteristic of summer and winter. At the coastal area of Quang Nam, the model is verified with measured wave data series in the summer period. Therefore, the results of the characteristics of wave field are great reliable and can be referred by other researches of this coastal area.